Uma análise sobre as questões ambientais nas empresas juniores da Universidade Federal de Lavras – MG - Pereira, Raphaella Reis (2022)
The consolidation of a company these days is no longer solely related to the possibility of earnings and pure and simple profitability. When structuring, creating a company, the entrepreneur and his entire management team, need to keep in mind the scopes necessary for the commitment with the sustainable development of the locality where it is installed, while they must also seek to adapt to a conscious use of the natural resources that are used in its interior. In this context, it is worth saying that Environmental Education (EA) can be understood as the means that directs man and society towards a sustainable construction of values, knowledge, skills and attitudes aimed at seeking a common good, capable of stimulating conservation of the environment. And the formation of a company, so to speak, must be in accordance with the social demands that are so present and necessary for everyone today. Thus, focusing on the business and environmental sector, it becomes increasingly important to encourage the creation and maintenance of Junior Companies (EJs) in Universities. Companies that are characterized as a non-profit civil association, formed and managed by students of a higher education course. It is worth noting that, in Junior Companies, students will often begin to be prepared for the job market. This research aims to know and analyze the performance of Junior Companies (EJs) of UFLA with regard to the environmental issue in their projects and in the training of participants. It also seeks to correlate the importance of actions related to post-consumer reverse logistics with the action of Junior Companies, as a way of showing that this socio-environmental responsibility is connected with planning and with the stipulation of growth goals, to which social responsibility of these companies, is structured from an action more connected with the construction of a fairer, egalitarian and equitable social environment for all. The methodology is based on a qualitative research with interviews with active members, participants of Junior Companies, who voluntarily responded to the questions asked, and also through the analysis of regulations and documents made available; The results showed that the behavior of Junior Companies has, in general, been inclined to the requirements of environmental causes, and this action has been recognized and improved throughout its development.